2019
DOI: 10.3389/fncel.2018.00498
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC1 Silence Promotes Neuroprotective Effects of Human Umbilical Cord-Derived Mesenchymal Stem Cells in a Mouse Model of Traumatic Brain Injury via PI3K/AKT Pathway

Abstract: Stem cell transplantation is a promising therapy for traumatic brain injury (TBI), but low efficiency of survival and differentiation of transplanted stem cells limits its clinical application. Histone deacetylase 1 (HDAC1) plays important roles in self-renewal of stem cells as well as the recovery of brain disorders. However, little is known about the effects of HDAC1 on the survival and efficacy of human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) in vivo. In this study, our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…MSCs, as a source of seed cells, have garnered increasing attention in the eld of stem cell therapy. At present, a large number of studies have discussed the clinical e cacy of stem cell therapy [21][22][23]; however, the safety and effectiveness of the optimal route for HUC-MSC transplantation have not been extensively considered. The safety of MSC administration has been reported in numerous clinical trials [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs, as a source of seed cells, have garnered increasing attention in the eld of stem cell therapy. At present, a large number of studies have discussed the clinical e cacy of stem cell therapy [21][22][23]; however, the safety and effectiveness of the optimal route for HUC-MSC transplantation have not been extensively considered. The safety of MSC administration has been reported in numerous clinical trials [24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…MSC‐derived exosomes have also been tested in porcine model of TBI coupled with hemorrhagic shock; consistent with the rodent data, the pigs had fewer cognitive deficits as determined with a neurological severity score and recovered faster than nontreated pigs . There is also evidence for MSC inducing immune suppression and anti‐inflammation; stimulating neurogenesis and angiogenesis; activating survival pathways and inhibiting apoptotic pathways; and enhancing neuroplasticity through neurite outgrowth and synaptogenesis …”
Section: Cell Therapy In Tbimentioning
confidence: 54%
“…When MSCs were transplanted into TBI rats, it was observed that the cells improved neurological function . Report also indicates that treatment of TBI with MSCs or histone deacetylase 1 silenced MSCs promotes neuroprotection and reduced oxidative stress . The study reveals that the neuroprotective effect acts via inhibition of the P13K/AKT pathway.…”
Section: Mesenchymal Stromal Cells In Traumatic Brain Injurymentioning
confidence: 82%
“…44 Report also indicates that treatment of TBI with MSCs or histone deacetylase 1 silenced MSCs promotes neuroprotection and reduced oxidative stress. 45 The study reveals that the neuroprotective effect acts via inhibition of the P13K/AKT pathway. In another study, treatment of TBI mice with MSCs stimulates the injured brain to induce trophic events that resulted in improvement in neurological function.…”
Section: Mesenchymal Stromal Cells In Traumatic Brain Injurymentioning
confidence: 95%